Evaluating the Effectiveness of Mobile Game-Based Learning for Raising Adolescent Health Awareness: The Case of "AHlam Na 2.0" - Noel Caliston (IJOEM: Indonesian Journal of E-learning and Multimedia, 2025)
This study addresses a critical gap in adolescent health education strategies in the Philippines, as highlighted by the Young Adult Fertility and Sexuality (YAFS) survey series, which overlooks the use of games as a medium for disseminating health information. To bridge this gap, the research introduces AHlam Na, a game-based mobile application designed to enhance adolescents' awareness and understanding of key health-related topics. Using a single-group pretest-posttest design, the study involved forty junior high school students from a randomly selected school in the Philippines. They interacted with the application that embedded adolescent health topics into its gameplay. Data collected through pretest and post-test surveys revealed a significant improvement in the student's knowledge and attitudes toward adolescent health after engaging in the game, indicating that game-based learning effectively enhances their learning experience. The positive reception and knowledge gains suggest that AHlam Na is a promising tool for promoting adolescent health awareness. Based on these findings, it is recommended that the application be integrated into the adolescent health curriculum in schools across the Philippines. Future studies should examine the long-term impact of game-based learning on health behaviors and expand the sample size to include more diverse demographic groups. This research contributes to the growing body of literature on game-based learning in health education by demonstrating the potential of digital games to address the limitations of traditional teaching methods. The successful implementation of AHlam Na underscores the importance of exploring gamified learning tools to deliver critical health information to young people effectively.